Sistem Pendukung Keputusan Penentuan Karyawan Terbaik Dengan Metode Topsis Pada PT Zafran Athmar Anugrah - Apriadi, Wahyu; Fransiska Prihatini Sihotang, Fransiska (MDP Student Conference, 2024)
PT. Zafran Athmar Anugrah is a company engaged in the property sector, namely as a housing developer (developer) which has approximately 40 employees which are divided into several division, namely the operational division, engineering division and marketing division. PT. Zafran Athmar Anugrah conducts the selection of the best employees to spur the spirit of employees in increasing their dedication and performance. The selection of the best employees is carried out periodically, namely every year but is not optional in its implementation because there are obstacles in calculating the value of the criteria in choosing the best employee, determining the best employee that is not transparent and takes a long time to determine it. Therefore, the author helps solve the problem by building a Decision Support System for determining the best employee with topsis method at PT Zafran Athmar Anugrah. This development process uses the Rational Unified Process (RUP) method. At the initial analysis stage using PIECES dan Usecase Diagram. At the design stage using Activity Diagram and Class Diagram. System development using Visual Studio Code, MySQL, dan Laravel as a framework with PHP programming language.